sigma-bishomoaromatic heterocycles: Reactivity and synthesis of 3-oxatetracyclo[3.3.0.0(2,8)0(4,6)]octane by photolysis at 185 nm - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 1996)
The title compound 5 was produced by 185 nm photolysis of 8. The products of the 185 nm photolysis can be rationalized by the assumption of the two diradical intermediates 16 and 17. Ar a temperature between 150 and 200 degrees C 5 reacts with fumaronitrile 23 to give the adducts 7 and 26 in a ratio of about (5 : 1). The kinetic analysis of this reaction shows, that the adduct 7 is formed by 1.3 dipolar cycloaddition of intermediate carbonyl ylide 6.
Keywords: PHOTOCHEMISTRY; OXIDES